Suspected Phenobarbital‐Induced Pseudolymphoma in a Dog. (2nd September 2017) - Lampe, R.; Manens, J.; Sharp, N.
Abstract : Pseudolymphoma is a drug reaction to anti‐epileptics that is well recognized in humans; it has been reported in one cat but not dogs. In this report, lymphoma‐like clinical signs are suspected to be secondary to phenobarbital administration in a dog. A 2.5‐year‐old male, neutered Shepherd mix presented for a 3‐day history of progressive ataxia, dazed mentation, pyrexia, and lethargy. While hospitalized, the dog developed generalized lymphadenopathy and sustained pyrexia. The dog was receiving levetiracetam and phenobarbital for epilepsy, and serum concentrations of both were within standard therapeutic ranges. Abdominal ultrasound revealed hepatomegaly, splenomegaly, and generalized lymphadenopathy. Cytology of the peripheral lymph nodes was consistent with reactive lymph nodes, and aspirates of the liver and spleen revealed histiocytic‐neutrophilic inflammation. Phenobarbital was discontinued and replaced with zonisamide. Within 24 hours, the dog was normothermic, and other clinical signs resolved within a week. This case highlights a potentially serious yet reversible adverse reaction to phenobarbital in a dog. This idiosyncratic reaction could be mistaken for neoplasia and is an important differential for lymphoma‐like signs in any dog administered phenobarbital.